Modified activated carbon, preparation method thereof and water purifier

By introducing anionic functionalized materials and crosslinking agents into activated carbon to form a gel network structure, the problem of poor adsorption of hard ions by activated carbon filter element is solved, and the hard ions and heavy metals are efficiently removed, which improves water flux and extends the service life of the filter element.

CN120268370APending Publication Date: 2025-07-08NINGBO FOTILE KITCHEN WARE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410027637.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-08
Publication Date
2025-07-08

AI Technical Summary

Technical Problem

The existing activated carbon filters are not effective when removing hardness ions such as calcium and magnesium ions in water, and the traditional extrusion process leads to clogging of micropores, reducing adsorption effect.

Method used

Anionic functionalized materials and crosslinking agents are used to form a gel network structure, combined with activated carbon, penetrate into the activated carbon pores through the modified liquid, forming a three-dimensional network, and combining amine functionalized materials to enhance adsorption performance.

Benefits of technology

The adsorption efficiency of hardness ions is improved, the hardness of water is reduced, the water flux is increased, and the modification process is stabilized through acidification treatment, scale generation is reduced, and the filter element life is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120268370A_ABST
    Figure CN120268370A_ABST
Patent Text Reader

Abstract

The invention discloses modified activated carbon, a preparation method thereof and a water purifier. The modified activated carbon comprises activated carbon and a gel network, and the gel network is distributed in pore channels of the activated carbon and is of a three-dimensional network structure formed by connecting anion functional materials together through a cross-linking agent. The modified activated carbon effectively solves the problem of low-cost and high-efficiency removal of hardness ions in drinking water, reduces water flux loss, and prolongs the service life of a filter element and a water purifier.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to modified activated carbon and a preparation method thereof, and a water purifier. Background Art

[0002] Due to the presence of hardness ions such as calcium and magnesium in water, scale is easily precipitated in heating and other usage scenarios, which affects the quality of people's drinking water and shortens the service life of related electrical equipment. Activated carbon has extremely strong adsorption properties due to its huge specific surface area and developed pore structure. At the same time, the chemical and physical properties of activated carbon are very stable. It is generally insoluble in strong acids or strong bases, and can still maintain good stability and adsorption properties in acidic and alkaline environments. Therefore, activated carbon is an excellent adsorbent that has not yet been found to have mature alternatives in many fields (military industry, gas and water treatment, etc.). Traditional activated carbon filters are not effective in removing hardness ions. How to improve the effect of activated carbon filters in removing hardness ions such as calcium and magnesium in water is a technical problem that needs to be solved urgently.

[0003] At present, the existing technology mainly uses the extrusion process to prepare modified activated carbon filter elements. In the extrusion process, the surface of the activated carbon filter element will be melted and wrapped by the hot-melt resin at high temperature, blocking the activated carbon micropores, thereby reducing the hardness ion adsorption effect. For example, CN110075616A provides a preparation method of a graphene-activated carbon composite filter element, which mixes coconut shell activated carbon powder, plastic rubber powder and graphene powder for pre-grafting, pours the mixed carbon powder into a compressed activated carbon filter element production equipment, and after sufficient stirring and heating, performs grafting modification treatment, extrusion, and cutting into graphene-coconut shell activated carbon carbon rods of a certain length. The CaCl2 adsorption effect of the graphene-activated carbon composite filter element activated carbon prepared by the extrusion process is not good. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the defect that the activated carbon in the prior art cannot efficiently and stably remove hardness ions, and to provide a modified activated carbon and its preparation method, and a water purifier. The activated carbon modification method of the present invention retains the pore structure of the activated carbon, and the presence of the cross-linking agent also ensures that the hardness ion adsorption material is stably retained in the activated carbon and is not easy to lose, and the raw material infiltrates into the activated carbon in the form of liquid, which has a higher mixing uniformity than that at the particle level and a better effect.

[0005] The present invention solves the above technical problems through the following technical solutions:

[0006] The invention provides a modified activated carbon, which comprises activated carbon and a gel network, wherein the gel network is distributed in the pores of the activated carbon and is a three-dimensional network structure formed by connecting anionic functionalized materials together through a crosslinking agent.

[0007] The present invention also provides a modified activated carbon, which comprises activated carbon and a gel network, and the gel network is distributed in the pores of the activated carbon. The gel network is a three-dimensional network structure formed by connecting an anion-functionalized material and an amine-functionalized material through a cross-linking agent.

[0008] The present invention also provides a method for preparing the modified activated carbon, which comprises the following steps:

[0009] S1, mixing the activated carbon with a modified liquid formed by an anion-functionalized material, a cross-linking agent and a solvent, and then heating and reacting to obtain a cross-linked product;

[0010] Calculated by the mass fraction of each component in the total mass of the modified liquid, the mass fraction of the anion-functionalized material is 1-20%;

[0011] The mass fraction of the cross-linking agent is 1-10%;

[0012] Alternatively, calculated by the molar ratio, the molar ratio of the anion-functionalized material to the cross-linking agent is (4-6):(1-4);

[0013] S2, acidifying the cross-linked product, and that's it.

[0014] In this solution, first using an anion-functionalized material, etc. to obtain a cross-linked product and then acidifying, instead of directly using the acidified anion-functionalized material as a modifier, has the following advantages: ① Since the anion-functionalized material is in a salt form, using the anion-functionalized material to modify the activated carbon has a better affinity with the activated carbon matrix and is more conducive to the penetration and combination of the two; ② Using the acidified anion-functionalized material, it is prone to ion exchange side reactions with the impurities contained in the activated carbon itself during the reaction, and acid will be generated in the product, thereby reducing the pH value of the system. However, using the anion-functionalized material for modification has little effect on the pH value, and the modification process is relatively stable; ③ The activated carbon itself contains impurities such as ash, and it needs to be purified by pickling during its preparation process. The final acidification in the present invention can not only convert the anion-functionalized material from sodium salt to acid, improve the efficiency of subsequent ion exchange, reduce the sodium concentration in the produced water, dissolve the scale on the surface of the end-stage nanofiltration membrane or reverse osmosis membrane, relieve the flux decline, but also purify the modified activated carbon.

[0015] In the present invention, preferably, step S1 satisfies one or more of the following conditions:

[0016] ① The raw materials of the modified liquid further include an amine-functionalized material;

[0017] Preferably, the amine-functionalized material includes one or at least two combinations of ethylenediamine, polyethyleneimine, polyallylamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, polyvinylimidazole.

[0018] Preferably, the mass fraction of the amine-functionalized material is 1-20%, for example 5%.

[0019] In this solution, the amine-functionalized material can adsorb heavy metals through the chelation of amino groups with heavy metals, enabling the modified activated carbon to efficiently filter out heavy metal ions in water; and because the amine-functional material is hydrophilic, it can reduce the resistance of water passing through the activated carbon and increase the water flux.

[0020] ② The anion-functionalized material includes one or a combination of at least two of sodium polystyrene sulfonate, sodium polyacrylate, and polyepoxysuccinic acid sodium.

[0021] ③ The mass fraction of the anion-functionalized material is 5%.

[0022] In this solution, the anion-functionalized material can exchange ions with calcium and magnesium ions in water, thus playing a role in reducing hardness; and because the anion-functional material itself has the ion exchange function with cations and hydrophilicity, it can remove some heavy metals and increase the water flux.

[0023] ④ The crosslinking agent includes one or a combination of at least two of glycidyltrimethylammonium chloride, glycidyltriethylammonium chloride, glycidyldimethyldodecylammonium chloride, glutaraldehyde, ethylene oxide, epichlorohydrin, ethylene glycol diglycidyl ether, glycerol glycidyl ether, and glycidyl methacrylate.

[0024] ⑤ The mass fraction of the crosslinking agent is 2%.

[0025] In this solution, the crosslinking agent can crosslink with other components in the modification liquid such as the anion-functional material to form a gel network that stably exists in the activated carbon to avoid the loss of components during use. Taking sodium polystyrene sulfonate and epichlorohydrin as the anion-functionalized material and the crosslinking agent respectively, the reaction process of the two crosslinking into a gel network is as follows. Among them, the wavy line (~) in the gel network chemical formula represents the chain segment after the crosslinking agent ring opens.

[0026]

[0027] Taking sodium polystyrene sulfonate, epichlorohydrin, and polyallylamine as the anion-functionalized material, the crosslinking agent, and the amine-functionalized material respectively, the reaction process of the three crosslinking into a gel network is as follows.

[0028] Among them, the wavy line (~) in the gel network chemical formula represents the chain segment after the crosslinking agent ring opens.

[0029]

[0030] ⑥ The solvent includes one or a combination of at least two of water, dimethylacetamide, dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone;

[0031] ⑦ The mass fraction of the solvent is 50-95%, for example, 88%.

[0032] In the present invention, preferably, the modification liquid includes 1-20% of the anionic functional material, 1-10% of the crosslinking agent, 1-20% of the amine functional material, and 50-95% of the solvent;

[0033] Preferably, the modification liquid includes 5% of sodium polystyrene sulfonate, 2% of glutaraldehyde, 5% of polyallylamine, and 88% of water.

[0034] In the present invention, preferably, in terms of molar ratio, the molar ratio of the anionic functional material, the crosslinking agent, and the amine functional material is (4-6):(1-4):(5-20);

[0035] In step S1, preferably, one or more of the following conditions are satisfied:

[0036] ① The formation process of the modification liquid is to sequentially put the raw materials into a stirring kettle and stir until uniform;

[0037] Preferably, the stirring time is 2-4 h, for example, 4 h;

[0038] Preferably, the stirring temperature is 20-30 °C, for example, 30 °C;

[0039] ② The mixing is to soak the activated carbon in the modification liquid;

[0040] Preferably, the soaking time of the activated carbon in the modification liquid is 15-45 min, for example, 30 min;

[0041] ③ After the mixing, the activated carbon is also soaked in pure water;

[0042] Preferably, the soaking time in pure water is 1-3 min, for example, 2 min;

[0043] ④ The heating reaction is to heat the activated carbon in an oven;

[0044] Preferably, the heating temperature is 60-90 °C, for example, 70 °C;

[0045] Preferably, the heating time is 1-5 h, for example, 2 h.

[0046] In step S1, preferably, the activated carbon is the washed activated carbon;

[0047] Preferably, the cleaning is to clean the activated carbon with pure water;

[0048] Preferably, the volume of the pure water used for cleaning is 20 times that of the activated carbon;

[0049] In step S1, preferably, the activated carbon is granular activated carbon and / or powdered activated carbon;

[0050] The particle size of the activated carbon is 20 - 300 mesh, BET ≥ 1000 g / m 2 , iodine value ≥ 1000 mg / g. For example, the particle size of the activated carbon is 20 - 50 mesh, BET is 1100 g / m 2 , and the iodine value is 1200 mg / g.

[0051] In the present invention, preferably, step S2 satisfies one or more of the following conditions:

[0052] The acidification is carried out in an acidification tank;

[0053] The acid used in the acidification is hydrochloric acid and / or sulfuric acid;

[0054] The mass fraction of the acid is 1 - 20%, for example 10%, and the concentration is mass percentage concentration;

[0055] The time of the acidification is 20 - 200 min, for example 30 min.

[0056] The present invention further provides a modified activated carbon, which is prepared by the above - mentioned method for preparing modified activated carbon.

[0057] The present invention also provides a water purifier, which includes the modified activated carbon as described above.

[0058] Among them, the water purifier sequentially includes the polypropylene filter element, the filter element containing the modified activated carbon, the nanofiltration filter element and the post - activated carbon filter element;

[0059] Or, the water purifier sequentially includes the polypropylene filter element, the filter element containing the modified activated carbon, the reverse osmosis filter element and the post - activated carbon filter element.

[0060] In this solution, the polypropylene filter element can filter out colloids, large particles, etc. in water.

[0061] In this solution, the nanofiltration filter element or the reverse osmosis filter element can filter out heavy metals, organic pollutants and other substances in water.

[0062] In this solution, the post - activated carbon filter element can improve the taste.

[0063] The positive and progressive effects of the present invention are as follows:

[0064] (1) Efficiently reduce water hardness: The activated carbon is modified by using an anion-functionalized material and a cross-linking agent, and the activated carbon is acidified, so that the anion-functionalized material is converted from a sodium salt to an acid, enabling the modified activated carbon to efficiently filter out hardness ions such as calcium and magnesium in water. Among them, the anion material can exchange ions with calcium and magnesium ions in water, thereby playing a role in reducing water hardness; and the acid generated by the exchange can effectively dissolve the water scale generated on the surface of the subsequent filter element during use, improving the service life.

[0065] (2) Improve the flux of activated carbon: Since the anion-functional material itself has hydrophilicity, it can reduce the resistance of water passing through the activated carbon substrate and improve the product water flux.

[0066] (3) All raw materials of the functionalized matrix are put in at one time, the preparation process is simple, and the cost is low. Description of the Drawings

[0067] Figure 1 It is a graph showing the change trend of the COD dissolution value of Effect Example 3 with the soaking time. Detailed Embodiments

[0068] The present invention will be further described below by way of examples, but the present invention is not limited to the scope of the described examples.

[0069] Example 1

[0070] Use pure water with a volume 20 times that of the activated carbon to be cleaned to clean the activated carbon with a particle size of 20 - 50 mesh and a BET of 1100 g / m 2 , and an iodine value of 1200 mg / g to obtain clean activated carbon. In this example, the molar ratio of sodium polystyrene sulfonate to glutaraldehyde is 5:4. Sodium polystyrene sulfonate, glutaraldehyde, and water (after conversion, the feeding amounts are 5% sodium polystyrene sulfonate, 2% glutaraldehyde, and 93% water by mass ratio) are successively put into a stirring kettle and stirred at an ambient temperature of 30 °C for 4 h until uniform to prepare a modified solution. The cleaned activated carbon is placed in the stirred modified solution, soaked for 30 min, and then soaked in pure water for 2 min. Then it is placed in an oven at 70 °C and heated for 2 h to initiate the cross-linking reaction of the modifier. And the cross-linked product is placed in an acidification pool with a mass concentration of 10% hydrochloric acid for acidification for 30 min, and finally washed and dried to obtain the modified activated carbon.

[0071] The modified activated carbon includes activated carbon and a gel network. The gel network is distributed in the pores of the activated carbon and is a three-dimensional network structure formed by connecting anion-functionalized materials through a cross-linking agent.

[0072] Example 2

[0073] Wash activated carbon with a particle size of 20 - 50 mesh and a BET of 1100 g / m² and an iodine value of 1200 mg / g with pure water having a volume 20 times that of the activated carbon to be cleaned to obtain clean activated carbon. 2 In this example, the molar ratio of polyallylamine, sodium polystyrenesulfonate and glutaraldehyde is 20:5:4. Polyallylamine, sodium polystyrenesulfonate, glutaraldehyde and water (after conversion, the feeding amounts are 5% polyallylamine, 5% sodium polystyrenesulfonate, 2% glutaraldehyde, 88% water by mass ratio) are sequentially added into a stirring kettle and stirred for 4 h at an ambient temperature of 30 °C until homogeneous to prepare a modified liquid. Place the clean activated carbon in the well-stirred modified liquid, soak for 30 min, and then soak in pure water for 2 min. Then place it in an oven at 70 °C and heat for 2 h to initiate the cross-linking reaction of the modifier. And place the cross-linked product in a hydrochloric acid acidification tank with a mass concentration of 10% and acidify for 30 min. Finally, after cleaning and drying, modified activated carbon is obtained.

[0074] The modified activated carbon includes activated carbon and a gel network. The gel network is distributed in the pores of the activated carbon and is a three-dimensional network structure formed by connecting anionic functional materials and amine functional materials through a cross-linking agent.

[0075] Comparative Example 1:

[0076] Wash activated carbon with a particle size of 20 - 50 mesh and a BET of 1100 g / m² and an iodine value of 1200 mg / g with pure water having a volume 20 times that of the activated carbon to be cleaned to obtain clean activated carbon. 2 In this comparative example, the molar ratio of polyallylamine and glutaraldehyde is 5:1. Polyallylamine, glutaraldehyde and water (after conversion, the feeding amounts are 5% polyallylamine, 2% glutaraldehyde, 93% water by mass ratio) are sequentially added into a stirring kettle and stirred for 4 h at an ambient temperature of 30 °C until homogeneous to prepare a modified liquid. Place the clean activated carbon in the well-stirred modified liquid, soak for 30 min, and then soak in pure water for 2 min. Then place it in an oven at 70 °C and heat for 2 h to initiate the cross-linking reaction of the modifier. And place the cross-linked product in a hydrochloric acid acidification tank with a mass concentration of 10% and acidify for 30 min. Finally, after cleaning and drying, modified activated carbon is obtained.

[0077] Comparative Example 2:

[0078] Wash activated carbon with a particle size of 20 - 50 mesh and a BET of 1100 g / m² 2, activated carbon with an iodine value of 1200 mg / g was obtained to get clean activated carbon. In this comparative example, the molar ratio of polyallylamine to sodium polystyrene sulfonate was 4:1. Polyallylamine, sodium polystyrene sulfonate, and water (after conversion, the feeding amounts were 5% polyallylamine, 5% sodium polystyrene sulfonate, and 90% water by mass ratio) were successively added into a stirring kettle and stirred for 4 h at 30 °C ambient temperature until homogeneous to prepare a modified solution. The clean activated carbon was placed in the stirred modified solution and soaked for 30 min, and then soaked in pure water for 2 min. Then it was placed in an oven at 70 °C and heated for 2 h to initiate the cross-linking reaction of the modifier. And the cross-linked product was placed in a hydrochloric acid acidification tank with a mass concentration of 10% for acidification for 30 min, and finally, it was washed and dried to obtain modified activated carbon.

[0079] Comparative Example 3:

[0080] Activated carbon with a particle size of 20 - 50 mesh and a BET of 1100 g / m was washed with pure water 20 times the volume of the activated carbon to be cleaned 2 , activated carbon with an iodine value of 1200 mg / g was obtained to get clean activated carbon. In this comparative example, the molar ratio of polyallylamine, polystyrene sulfonic acid, and glutaraldehyde was 20:5:4. Polyallylamine, polystyrene sulfonic acid, glutaraldehyde, and water (after conversion, the feeding amounts were 5% polyallylamine, 5% polystyrene sulfonic acid, 2% glutaraldehyde, and 88% water by mass ratio) were successively added into a stirring kettle and stirred for 4 h at 30 °C ambient temperature until homogeneous to prepare a modified solution. The clean activated carbon was placed in the stirred modified solution and soaked for 30 min, and then soaked in pure water for 2 min. Then it was placed in an oven at 70 °C and heated for 2 h to initiate the cross-linking reaction of the modifier, and finally, it was washed and dried to obtain modified activated carbon.

[0081] Comparative Example 4:

[0082] Activated carbon with a particle size of 20 - 50 mesh and a BET of 1100 g / m 2 , unmodified activated carbon with an iodine value of 1200 mg / g.

[0083] Effect Example 1:

[0084] The above cases were tested using the water efficiency test water, and the configuration method is detailed in GB34914. The results are shown in Table 1:

[0085] Table 1

[0086]

[0087] Compared with Comparative Example 1 and Comparative Example 4, in Example 1 and Example 2, due to the addition of anionic functionalized materials in the modified solution raw materials, the prepared activated carbon has good removal effects on calcium and magnesium ions and heavy metals.

[0088] Compared with Comparative Example 2, in Examples 1 and 2, due to the addition of a crosslinking agent to the raw materials of the modification liquid, the precipitation of the adsorbent material during use is effectively reduced, and the prepared modified activated carbon has a lasting removal effect on calcium and magnesium ions and heavy metals.

[0089] In Example 2 of the present invention, the activated carbon was first modified with a modification liquid to obtain a crosslinked product, and then the crosslinked product was acidified. Compared with Comparative Example 3, because: ① before acidification, the anionic functionalized material is in a salt form, and has a better affinity with the activated carbon matrix than the acid form anionic functionalized material after acidification, which is beneficial to the penetration and combination of the two; ② if the acid form anionic functionalized material is used in the modification stage, it is prone to ion exchange side reactions with the impurities contained in the activated carbon itself during the reaction, and acid will be generated in the product, thereby reducing the pH value of the system and affecting the stability of the reaction; while using the salt form anionic functionalized material, the product is a salt and has almost no effect on the pH value; ③ the activated carbon itself contains impurities such as ash, and it needs to be purified by pickling during its preparation process. Therefore, the modified activated carbon prepared in Example 2 has a better effect on removing hardness ions and heavy metals than Comparative Example 3.

[0090] Effect Example 2:

[0091] During the process of preparing the modification liquid in Example 1 (successively adding sodium polystyrene sulfonate with a mass ratio of 5%, glutaraldehyde with a mass ratio of 2%, and water with a mass ratio of 93% into a stirring kettle and stirring under the environmental temperature condition of 30°C), explore the relationship between the properties of the modification liquid and the stirring time and the dissolution situation during the preparation process, as follows:

[0092] Table 2 shows the changes in the properties of the modification liquid with the reaction time. It can be seen that when the reaction time is 0 - 6 hours, the modification liquid shows the Tyndall effect, indicating that a chemical reaction has occurred between the substances in the modification liquid, forming a gel-like crosslinked product; and it can be seen that during the process of the reaction time from 0h to 10h, as the solubility of the crosslinked product in the solvent gradually decreases, the modification liquid gradually changes from a colorless and transparent state to a precipitation state; correspondingly, the solution properties also change with the reaction time, and the turbidity and viscosity of the solution increase with the extension of the reaction time, which is mainly because the degree of reaction increases and the crosslinking degree of the crosslinked product increases, so the turbidity and viscosity of the solution increase.

[0093] It can be seen from this that during the stirring and preparation process of the modification liquid in Example 1, the reaction raw materials therein underwent a crosslinking reaction to generate a crosslinked product, and the crosslinked product is gel-like.

[0094] Table 2

[0095]

[0096] Note: In the table, " / " indicates that obvious aggregates are formed in the solution, so the turbidity and viscosity cannot be measured.

[0097] Effect Example 3:

[0098] In order to investigate the content or dissolution of small molecules or unreacted substances in the modified activated carbon, the modified activated carbon containing a gel network obtained in Example 1 was immersed in water, and the change trend of the COD dissolution value per unit time with the immersion time was tested.

[0099] The COD value is the difference in COD between the water sample after immersing the modified activated carbon and the original solution. The specific calculation method is: COD value = COD value of the water sample after immersion - COD value of the raw water.

[0100] The sampling method is to replace the water with fresh water for immersion after each sampling point. Therefore, by comparing the results of multiple rounds of immersion, it can be seen that the COD difference is higher in the early stage and smaller in the later stage, indicating that the reaction products in the modified activated carbon after cleaning the residual raw materials can exist stably and are not easily dissolved.

[0101] Specifically, as can be seen from Figure 1 , when the immersion time is 0 h, the COD difference is relatively high because small molecules dissolve rapidly. These small molecules are mainly the solvents of the reaction solution. Between the immersion time of 0 h and 20 h, the COD value remains between 0 - 5.5 ppm, mainly due to the dissolution of macromolecules such as reaction raw materials. After soaking for 25 h, the low COD value indicates that there is less residual reaction raw material and the reaction is sufficient. The results show that the gel network formed by cross-linking polymerization can exist stably in the modified activated carbon and has a low dissolution rate.

[0102] Although the specific implementation manners of the present invention have been described above, those skilled in the art should understand that this is only for illustration purposes. The protection scope of the present invention is defined by the appended claims. Without departing from the principles and essence of the present invention, those skilled in the art can make various changes or modifications to these implementation manners, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A modified activated carbon, characterized in that, It includes activated carbon and a gel network, and the gel network is distributed in the pores of the activated carbon. The gel network is a three-dimensional network structure formed by connecting anion-functionalized materials together through a cross-linking agent.

2. A modified activated carbon, characterized in that, It includes activated carbon and a gel network, and the gel network is distributed in the pores of the activated carbon. The gel network is a three-dimensional network structure formed by connecting anion-functionalized materials and amine-functionalized materials together through a cross-linking agent.

3. A preparation method of modified activated carbon, characterized in that, It includes the following steps: S1. Mix the activated carbon with a modified liquid formed by an anion-functionalized material, a cross-linking agent, and a solvent, and then heat and react to obtain a cross-linked product; Calculated by the mass fraction of each component in the total mass of the modified liquid, the mass fraction of the anion-functionalized material is 1-20%; The mass fraction of the cross-linking agent is 1-10%; Alternatively, calculated by the molar ratio, the molar ratio of the anion-functionalized material to the cross-linking agent is (4-6):(1-4); S2. Acidify the cross-linked product, and that's it.

4. The preparation method of the modified activated carbon according to claim 3, characterized in that In step S1, the raw materials of the modified liquid further include an amine-functionalized material; Preferably, the amine-functionalized material includes one or a combination of at least two of ethylenediamine, polyethyleneimine, polyallylamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, and polyvinylimidazole; Preferably, the mass fraction of the amine-functionalized material is 1-20%, such as 5%; And / or, the anion-functionalized material includes one or a combination of at least two of sodium polystyrene sulfonate, sodium polyacrylate, and sodium polyepoxysuccinate; And / or, the mass fraction of the anion-functionalized material is 5%; And / or, the cross-linking agent includes one or a combination of at least two of glycidyltrimethylammonium chloride, glycidyltriethylammonium chloride, glycidyldimethyldodecylammonium chloride, glutaraldehyde, ethylene oxide, epichlorohydrin, ethylene glycol diglycidyl ether, glycerol glycidyl ether, and glycidyl methacrylate; And / or, the mass fraction of the cross-linking agent is 2%; And / or, the solvent includes one or a combination of at least two of water, dimethylacetamide, dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone; And / or, the mass fraction of the solvent is 50-95%, such as 88%.

5. The preparation method of the modified activated carbon according to claim 3, characterized in that, The modified liquid includes 1-20% of the anion-functionalized material, 1-10% of the cross-linking agent, 1-20% of the amine-functionalized material, and 50-95% of the solvent; Preferably, the modified liquid includes 5% of sodium polystyrene sulfonate, 2% of glutaraldehyde, 5% of polyallylamine, and 88% of water; Alternatively, calculated by the molar ratio, the molar ratio of the anion-functionalized material, the cross-linking agent, and the amine-functionalized material is (4-6):(1-4):(5-20).

6. The method for preparing the modified activated carbon according to claim 3 or 4, characterized in that, In step S1, the formation process of the modified liquid is to sequentially put the raw materials into a stirring kettle and stir until uniform; Preferably, the stirring time is 2-4 h, such as 4 h; Preferably, the stirring temperature is 20-30 °C, such as 30 °C; And / or, the mixing is to soak the activated carbon in the modified liquid; Preferably, the soaking time of the activated carbon in the modification liquid is 15 - 45 min, such as 30 min; And / or, after mixing, the activated carbon is also soaked in pure water; Preferably, the soaking time in pure water is 1 - 3 min, such as 2 min; And / or, the heating reaction is to heat the activated carbon in an oven; Preferably, the heating temperature is 60 - 90 °C, such as 70 °C; Preferably, the heating time is 1 - 5 h, such as 2 h.

7. The preparation method of the modified activated carbon according to claim 3, characterized in that, In step S1, the activated carbon is the washed activated carbon; Preferably, the washing is to wash the activated carbon with pure water; Preferably, the volume of pure water used for washing is 20 times that of the activated carbon; And / or, the activated carbon is granular activated carbon and / or powdered activated carbon; And / or, the particle size of the activated carbon is 20 - 300 mesh, BET ≥ 1000 g / m 2 , iodine value ≥ 1000 mg / g. For example, the particle size of the activated carbon is 20 - 50 mesh, BET is 1100 g / m 2 , and the iodine value is 1200 mg / g.

8. The preparation method of the modified activated carbon according to claim 3, characterized in that, The acidification satisfies one or more of the following conditions: The acidification is carried out in an acidification tank; The acid used in the acidification is hydrochloric acid and / or sulfuric acid; The concentration of the acid is 1 - 20%, such as 10%, and the concentration is mass percentage concentration; The acidification time is 20 - 200 min, such as 30 min.

9. A modified activated carbon, characterized in that, The modified activated carbon is made by the preparation method according to any one of claims 3 - 8.

10. A water purifier, which comprises the modified activated carbon according to any one of claims 1 - 2 or claim 9; Among them, The water purifier sequentially comprises a polypropylene filter element, a filter element containing the modified activated carbon, a nanofiltration filter element, and a post - placed activated carbon filter element; Or, the water purifier sequentially comprises a polypropylene filter element, a filter element containing the modified activated carbon, a reverse osmosis filter element, and a post - placed activated carbon filter element.

Citation Information

Patent Citations

  • Graphene-activated carbon composite filter element as well as preparation method and application thereof

    CN110075616A